HLA-DQA1*04:01 is related to a higher multiple sclerosis lesion load on T2/Flair MRI sequences - Fabio NORO; Soniza Vieira ALVES-LEON; Fabricia Lima FONTES-DANTAS; Paulo Roberto VALLE BAHIA; Rodrigo Ferrone ANDREIUOLO; Fernanda Cristina RUEDA LOPES; Valeria Coelho Santa Rita PEREIRA; Livia de Almeida Afonso ABI-HAILA; Renan Amaral COUTINHO; Amanda Dutra de ARAUJO; Edson MARCHIORI (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The genetic predisposition to multiple sclerosis (MS) is associated with HLA alleles, especially HLA-DRB1*15:01. Objective: To identify associations between findings in magnetic resonance imaging (MRI) and genetic features in a Brazilian cohort of patients with MS. Methods: We retrospectively studied data from 95 consecutive patients with MS. Two independent observers who were blinded to the clinical data identified black holes and enhanced lesions on T1 MRI sequences, and counted and measured contrast-enhanced lesions on T2 and Flair (fluid attenuation inversion recovery) sequences. Cases were classified according to lesion size, number, and volume. The HLA-DRB1, HLA-DQB1, and HLA-DQA1 alleles, and the rs4774, rs3087456, rs6897932, rs731236, and rs1033182 single nucleotide polymorphisms were identified by polymerase chain reaction amplification with sequence-specific primers using the One Lambda Inc. Kit, Canoga Park, CA, USA. Results: Patients with the HLA-DQA1*04:01 allele had lesion load (adjusted for age, sex, and MS duration) above median compared with patients with other HLA-DQA1 alleles (p=0.02). There were no differences among all the other HLA alleles and single nucleotide polymorphisms and lesion load. Conclusions: The correlation of the HLA-DQA1*04:01 allele with a higher lesion load on T2/Flair MRI sequences suggests that the presence of this allele is associated with the risk of greater MS severity.